Indonesia Pasca-Konflik: Kekerasan Sosial, Perdamaian, dan Wacana Pembangunan Berkelanjutan - Muliono Muliono (Universitas Islam Negeri Imam Bonjol Padang, 2021)
This study discusses post-conflict society in Indonesia and the discourse of sustainable peace building as a way to build a post-conflict society. Important post-conflict studies are examined not only for the sake of recovery from the impact of violent conflict, but also for the potential for further violent conflict in new forms to have an impact on psychological and economic-socio-political instability. This study shows that the challenges of peace building in Indonesia in the post-conflict period are based on three main things, namely the past history, especially in areas with a history of large-scale conflicts; the pluralistic character of Indonesia in terms of ethnicity, religion, race and class; and, the new character of violent conflict that is based on the electoral democratic process. The practice of electoral democracy tends to arouse the passion of violent conflict, especially when the issues used touch the issue of identity politics. To that end, building a post-conflict society requires a preventive approach and peace consolidation (conflict transformation) through a sustainable development and empowerment agenda. This agenda must involve an empowerment paradigm via functional institutional development to organize various public needs and aspirations at the local level, as well as institutional development oriented to capacity building and community empowerment through a democratized and decentralized process.